Application of Scrum and PM Canvas in a Project-based Learning Approach - Ferreira, Costa (2020)
Project-based Learning (PBL) is a teaching and learning strategy that allows students to develop competences while working on projects. It is important to apply good management approaches in order to achieve all project and learning objectives. This paper presents an application of Scrum and Project Model Canvas (PM Canvas) to manage learning projects developed by teams of students in interaction with industrial companies. These projects are part of a Project-based Learning (PBL) approach developed in the fourth year of an integrated master program in Industrial Engineering and Management. A group of 5 students from the fifth year of the same degree gave support to the PBL teams regarding the utilization of these tools. The work was developed during one month with meetings every Fridays. These project management tools were applied to help the PBL teams to organize and share the tasks, as well as visualize and control the whole project. To evaluate the teams' performance and the way they are realizing the tasks, it was counted the number of tasks done in each weekday and the students were inquired in order to understand their perceptions of the use of these project management tools. The results revealed that the groups performed most of the tasks on Wednesday and the inquiry revealed that most of the PBL teams did not know and had never used project management tools. The inquiry also revealed that the project management tools were considered helpful for the control and organization of the project tasks, improving overall team performance.